The Distribution of Job Characteristics - Lucas, Robert E. B. (The Review of Economics and Statistics, 1974)
THIS paper presents a cross-sectional analysis of the distribution across population classes of of work performed in the United States. The novelty of the study resides in its measurement of types of work. The approach adopted is to focus on a matrix of coefficients describing the nature of the task involved in each occupation of a very fine occupational classification, the elements of which matrix are here referred to as characteristics. For example, the vector of job characteristics employed includes indicators of physical working conditions, repetitiveness, position on the hierarchy of relationships to people, and skill demands, inherent in a job. Sections II and III describe data sources and the process of compiling a data file, respectively. Section VI compares sample mean job characteristics by race and by sex, these being the mean values of the left-hand variables employed in section VII. The latter reports estimates of functions in the general class Zja= F(ga) + Ea (1) where Zja 1 if the occupation performed by person a has job characteristic j, 0 otherwise, ga a vector of attributes, or personal characteristics, of person a, Ea -a disturbance term. The vector ga includes race, sex, age, schooling and union membership. The particular specification chosen within the general class (1) is given in section IV, and V is a cautionary note on interpreting the results of sections VI and VII.